Non-compliant Reading and Annotating in the Ruthenian Reformation: Cyril of Jerusalem’s Mystagogical Catechisms from Szymon Budny’s Library - Ivanova, Maria (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2021)
While the works of the Antitrinitarian thinker and religious leader Szymon Budny (ca. 1530-93) have been the subject of extensive scholarly research, his library, marginalia, and reading practices have been significantly less examined. Following the discovery of a copy of Cyril of Jerusalem’s Mystagogical Catechisms (Vienna, 1560) belonging to Budny, I analyze Budny’s notes and comments regarding the Latin translation of Cyril’s text as a case study of Budny’s attempt to recover the Church Father from the Catholic post-Tridentine agenda and his own subsequent re-appropriation of Cyril for his radical non-adorantist program. By exploring Budny’s subversive reading and annotating strategies, I demonstrate Budny’s original contributions to the development of Antitrinitarian thought in Europe. I also illustrate how marginalia and paratexts reflect not only the history of the book in which they are found, but also how they throw light on religious and intellectual history.